Pharmaceutical Compounds in Wastewater: Wetland Treatment as a Potential Solution - John R. White; Marco A. Belmont; Chris D. Metcalfe (The Scientific World Journal)
Pharmaceutical compounds are being released into the aquatic environment through wastewater discharge around the globe. While there is limited removal of these compounds within wastewater treatment plants, wetland treatment might prove to be an effective means to reduce the discharge of the compounds into the environment. Wetlands can promote removal of these pharmaceutical compounds through a number of mechanisms including photolysis, plant uptake, microbial degradation, and sorption to the soil. We review relevant laboratory research on these various mechanisms and provide data on the few studies that have examined wetland removal. There is a need to document the degree to which various pharmaceutical compounds are removed in full-scale treatment wetlands, as there is a paucity of data on overall pharmaceutical removal rates.